Does Alcohol Consumption Influence People’s Perceptions of Their Own and a Drinking Partner’s Ability to Consent to Sexual Behavior in a Non-sexualized Drinking Context? - Jozkowski, Kristen N. (Journal of interpersonal violence, 2023)
The purpose of this study was to examine the extent that alcohol consumption affected participants’ perceptions of their own and their friend’s ability to consent to sex in a non-bar drinking environment. We interviewed 176 people at tailgates in dyads about their own and their friends’ alcohol consumption, intoxication symptoms, and ability to consent. Participants reported consuming a mean of 4.6 drinks and had a breath alcohol concentration (BrAC) of .075 on average, but few thought they or their friend had diminished cognitive function. Accordingly, 92.6% indicated they could consent to sex and 81.8% indicated their friend could consent to sex. Number of drinks people reported consuming, self-reported intoxication levels and symptoms, and BrACs were not significantly related to participants’ perceptions of their own or their friends’ ability to consent to sex. However, gender pairing of the dyad was significant; those in man–man pairs were more likely than those in woman–woman pairs to indicate their friend could consent and they would allow their friend to have sex if approached by an interested party. Participants also indicated that they did not perceive themselves or their friends to be “too intoxicated” as common reasons why they believed they and their friend could consent. Because alcohol-facilitated sexual assault is common among college students, we recommend sexual assault prevention educators focus on raising awareness regarding alcohol’s negative cognitive effects, particularly related to consent communication.